The effectivity of pandanus leaf extract for the treatment of sangkuriang catfish juvenile Clarias gariepinus infected by Aeromonas hydrophila - Sopiah, Siti; Rosidah, Rosidah; Lili, Walim; Iskandar, Iskandar; Suryadi, Ibnu Bangkit (Indonesian Society of Scientific Aquaculture (ISSA), 2018)
ABSTRACTThe aim of this study was to determine the effective concentration of pandanus Pandanus amaryllifolius leaf extract for the treatment of sangkuriang catfish juvenile infected by Aeromonas hydrophila. The method used in this study was an experimental method with completely randomized design consisted of five treatments and three replications. The treatments were A (control), B (400 mg/L), C (600 mg/L), D (800 mg/L), and E (1000 mg/L) trough immersion for 24 hours through immersion for 24 hours. The fish has infected with A. hydrophila bacteria as much as 20 mL of NaCl/L in 10 L of water medium with a density of 108 CFU/mL through immersion. The observed parameters were clinical symptoms, recovery process, survival rate, and water quality. The results showed that pandanus leaf extract at a concentration of 800 mg/L for 24 hours was effective for treating sangkuriang catfish juvenile that infected by A. hydrophila with a survival rate of 86.67%. Based on the regression analysis, it discovered that the optimum concentration of pandanus leaf extract through immersion for 24 hours was 774.39 mg/L and the predicted survival was 92.16%. Keywords: Aeromonas hydrophila, catfish fingerlings, effective concentration, infection, pandanus leaf extract ABSTRAKPenelitian ini bertujuan untuk menentukan konsentrasi yang efektif dari ekstrak daun pandan wangi Pandanus amaryllifolius untuk pengobatan benih lele sangkuriang Clarias gariepinus yang terinfeksi bakteri A. hydrophila. Metode yang digunakan dalam penelitian ini adalah metode eksperimental rancangan acak lengkap dengan lima perlakuan dan tiga ulangan. Perlakuan penelitian adalah A (kontrol), B (400 mg/L), C (600 mg/L), D (800 mg/L), dan E (1000 mg/L). Ikan uji diinfeksi bakteri A. hydrophila sebanyak 20 mL NaCl/L dalam 10 L media air dengan kepadatan 108 CFU/mL melalui perendaman selama 24 jam. Parameter yang diamati meliputi gejala klinis, waktu pulih, kelangsungan hidup, dan kualitas air. Hasil penelitian menunjukkan bahwa penggunaan ekstrak daun pandan wangi pada konsentrasi 800 mg/L selama 24 jam efektif untuk pengobatan benih lele sangkuriang yang terinfeksi bakteri A. hydrophila dengan tingkat kelangsungan hidup sebesar 86,67%. Berdasarkan analisis regresi diketahui bahwa konsentrasi optimum penggunaan ekstrak daun pandan wangi melalui perendaman selama 24 jam yaitu 774,39 mg/L dan prediksi kelangsungan hidup ikan adalah 92,16%. Kata kunci : Aeromonas hydrophila, benih lele sangkuriang, ekstrak daun pandan, infeksi, efektifitas konsentrasi